The Fate of Ten: Lorien Legacies #6 - Lore, Pittacus (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2015)
In order to thwart the Mogadorian invasion, a group of the Garde head to a pyramid in Mexico in order to awaken a power that can save the world.
"An I am number four book"--Spine.
Keywords: Extraterrestrial beings -- Fiction; Aliens (Fictional characters) -- Fiction; Science fiction